The Meaning of the Lyrics of the Song "Qolbi Fil Madinah" Through Charles Sanders Peirce's Semiotic Framework - Hasna Afifah Yustiana Yunasa; Rohanda Rohanda; Dendi Yuda S. (Gunung Djati Conference Series, 2025)
This study aims to uncover the deeper meanings embedded in the lyrics of the song “Qolbi Fil Madinah” through Charles Sanders Peirce’s semiotic framework and to explore its implications for the daily life of Muslims. The song was chosen due to its rich spiritual content and its strong reflective potential for listeners. The research employs a qualitative descriptive method with a semiotic analysis framework based on Peirce’s triadic model: representamen (sign), object, and interpretant. The findings reveal that the lyrics are filled with religious symbols—such as Madinah, shalawat, the Green Dome, and the figure of Prophet Muhammad SAW. which serve not only as aesthetic elements but also as carriers of moral and spiritual messages. These messages encourage listeners to increase their love for the Prophet, strengthen their spiritual connection, and cultivate noble character in everyday life. The song thus functions not only as entertainment but also as a medium for fostering Islamic character development in a contextual and emotionally resonant manner.